Nicotine Impaired Bone Histomorphometric Parameters And Bone Remodeling Biomarkers In Sprague-Dawley Male Rats - H, Hermizi; O, Faizah; S Ima, Nirwana; S Ahmad, Nazrun; DA , Luke; M, Norazlina (Microscopy Society of Singapore, 2007)
The effects of nicotine administration on structural and cellular parameters of bone histomorphometry, cotinine, and biomarkers of bone remodeling were studied in twenty-one Sprague-Dawley male rats. Rats aged three months and weighing between 250-300 g were divided into three groups. Group 1 was the baseline group, which was sacrificed without treatment. The other 2 groups were the control group and the nicotine group. The nicotine group was treated with nicotine 7 mg/kg body weight and the C group was treated with normal saline only. Treatment was given by intraperitoneal injection, six days a week for a period of 4 months. Histomorphometric analysis was done on the metaphyseal region of the trabecular bone of the left femur by using an image analyzer. Biochemical analysis was done using ELISA-test kit to compare the serum cotinine, osteocalcin and pyridinoline (PYD) levels between pretreatment and after 4 months treatment in the control and nicotine groups. Histomorphometric analysis revealed that nicotine significantly decreased the trabecular bone volume (BV/TV) and the osteoblast surface (Ob.S/BS), and increased the osteoclast surface (Oc.S/BS) and the eroded surface (ES/BS) compared to the baseline and control groups. In addition, biochemical analysis showed that nicotine treatment for 4 months significantly decreased the osteocalcin (bone formation marker) levels while the cotinine and PYD (bone resorption marker) levels were increased as compared to pretreatment. We concluded that treatment with nicotine 7 mg/kg for 4 months exerted negative a effect on the trabecular bone histomorphometric parameters and bone remodeling biomarkers.